INSECURITY AS PREDICTOR OF STUDENTS’ LEARNING IN ZAMFARA STATE, NIGERIA - OJELEYE, CHIOMA IFEOMA; KAURA, BELLO LADAN; GUSAU, BASIRA MUSA; ABDULLAHI, MURJANATU (Sokoto Educational Review, 2022)
The rate of insecurity in Nigeria is alarming to wonder Nigeria is listed as the second most terrorized nation in the world. The study examined the effect of insecurity on students’ learning in Zamfara state. The study employed to survey and cross-sectional research designs. Data were retrieved from 273 respondents utilizing snowballing sampling technique. Preliminary analyses such as multicollinearity test, normality test, common method bias and non-response bias test were assessed on the retrieved data while structural equation modelling (SEM-PLS) was used to test the hypothesized relationship. The finding revealed that personal insecurity has a negative and significant effect on students’ learning in Zamfara state. In the same vein, community insecurity has a negative and significant effect on students’ learning in Zamfara state. The study recommended that the Government across all tiers should take the personal security of its citizens seriously as it adversely affects the learning of students. This can be practically done by putting laws into effect that can assure the citizens of their safety.